PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTU PERMAINAN TEKA-TEKI BERANTAI TERHADAP HASIL BELAJARTEMATIK SISWA KELAS V SDN GAYAMSARI 01 SEMARANG - Aji Tulus Prasetyo; Sutrisno Sutrisno.; Mudzanatun Mudzanatun. (Jurnal Pesona Dasar, 2018)
This study aims to determine the effect of learning model Think Pair Share assisted puzzle game chain to result learn some vital lessons thematic graders V theme 6 "Human Organs and Animals" subthema 3 "Living Humans, Animals and Plants" in SDN Gayamsari 01 Semarang year 2017/2018 lesson. This type of research is a quantitative research study design Pre-ExperimentalDesign.Forms Pre-Experimental Design used in this research is the One-group pretest-posttestdesign.The population in this study were all students in grade 01 VB SDN Gayamsari Semarang academic year 2017/2018. The samples taken were 22 students of class VB using saturation sampling technique. The data in this study were obtained through testing. The results of the average value of pretest and posttest increased. On the pretest value that has been implemented is obtained an average value of 63,00 and the average post-test score of 90,00. Thus, an increase in thematic learning outcomes of students in using learning model Think Pair Share assisted puzzle game chain. Results of testing the hypothesis on the cognitive aspects of student learning outcomes showed thatt tcount7,930 andttable 2,074 with significance level of 5%. Because tcountttable is 7,930 2,074 then Ha acceptable means learning model Think Pair Share assisted puzzle game chain affects the outcome of the thematic learning VB grade students of SDN 01 Gayamsari Semarang.